CdSe/ZnS quantum dots as a booster in the active layer of distributed ternary organic photovoltaics - Lewińska, Gabriela; Jeleń, Piotr; Kucia, Zofia; Sitarz, Maciej; Walczak, Łukasz; Szafraniak, Bartłomiej; Sanetra, Jerzy; Marszalek, Konstanty W. (Beilstein Journal of Nanotechnology, 2024)
Organic solar cells are a promising candidate for practical use because of their low material cost and simple production procedures. The challenge is selecting materials with the right properties and how they interrelate in the context of manufacturing the device. This paper presents studies on CdSe/ZnS nanodots as dopants in a polymer–fullerene matrix for application in organic solar cells. An assembly of poly(3-hexylthiophene-2,5-diyl) and 6,6-phenyl-C71-butyric acid methyl ester was used as the active reference layer. Absorption and luminescence spectra as well as the dispersion relations of refractive indices and extinction coefficient were investigated. The morphologies of the thin films were studied with atomic force microscopy. The chemical boundaries of the ternary layers were determined by Raman spectroscopy. Based on UPS studies, the energy diagram of the potential devices was determined. The resistivity of the layers was determined using impedance spectroscopy. Simulations (General-Purpose Photovoltaic Device Model) showed a performance improvement in the cells with quantum dots of 0.36–1.45% compared to those without quantum dots.
Keywords: efficiency; luminescence; organic solar cells; quantum dots